Turning the Tide on Poverty: Community champions as critical elements of success in economically distressed communities. Issue 3 (26th May 2016) - Worthy, Sheri Lokken; Downey, Laura; Dyk, Patricia Hyjer; Monroe, Pamela A.; Tyler-Mackey, Crystal; Welborn, Rachel
Abstract: Turning the Tide on Poverty is designed in part to expand the number of new voices in community dialogs and to spur those individuals to become leaders in their communities. In this article, we explore the degree to which the success of the Tide project is linked to the emergence or presence of a local champion. We defined a champion as a catalyst or sparkplug and then examined the extant literature and our data to determine the qualities of a champion. When a person (or persons) who was enthusiastic, rallied others, and provided momentum and passion for the project emerged, that person often was identified by other community members as a key element in the success of Tide. We argue that such a person is a community champion and discuss our findings within the Community Capitals Framework. Implications for spurring improvements in distressed communities in the southern US are discussed.